Search for the Blazhko Effect in Field RR Lyrae Stars Using LINEAR and ZTF Light Curves - Ema Donev; Željko Ivezić (The Astronomical Journal)
We analyzed the incidence and properties of RR Lyrae stars that show evidence for amplitude and phase modulation (the so-called Blazhko Effect) in a sample of ∼3000 stars with LINEAR and ZTF light curve data collected during the periods of 2002–2008 and 2018–2023, respectively. A preliminary subsample of about ∼500 stars was algorithmically preselected using various data quality and light curve statistics, and then 228 stars were confirmed visually as displaying the Blazhko effect. This sample increases the number of field RR Lyrae stars displaying the Blazhko effect by more than 50% and places a lower limit of (11.4 ± 0.8)% for their incidence rate. We find that ab type RR Lyrae that show the Blazhko effect have about 5% (0.030 day) shorter periods than starting sample, a 7.1 σ statistically significant difference. We find no significant differences in their light curve amplitudes and apparent magnitude (essentially, signal-to-noise ratio) distributions. No period or other differences are found for c type RR Lyrae. We find convincing examples of stars where the Blazhko effect can appear and disappear on timescales of several years. With time-resolved photometry expected from the Legacy Survey of Space and Time, a similar analysis will be performed for even larger samples of field RR Lyrae stars in the southern sky and we anticipate a higher fraction of discovered Blazhko stars due to better sampling and superior photometric quality.